\(6x-5\left(x-7\right)=\left(27-514\right)-\left(486-73\right)\)
\(\Leftrightarrow6x-5x+35=27-514-486+73\)
\(\Leftrightarrow x=27-514-486+73-35\)
\(\Leftrightarrow x=-935\)
Đề bài : Tìm số nguyên x?
6x-5(x-7)=(27-514)-(486-73)
6x-5x+35=-900
x+35=-900
x=(-900)-35
x=-935
Vậy x=-935
\(\text{6x-5(x-7)=(27-514)-(486-73)}\)
\(6x-5\left(x-7\right)=27-514-486+73\)
\(6x-5\left(x-7\right)=\left(27+73\right)+\left(-514-486\right)\)
\(6x-5x+35=100+\left(-1000\right)\)
\(x+35=-900\)
\(\Rightarrow x=-900-35\)
\(\Rightarrow x=-935\)
học tốt
\(6x-5\left(x-7\right)=\left(27-514\right)-\left(486-73\right)\)
\(6x-5x+35=-487-413\)
\(x+35=-900\)
\(x=-935\)